2012
DOI: 10.3122/jabfm.2012.01.110148
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fiber for the Treatment of Type 2 Diabetes Mellitus: A Meta-Analysis

Abstract: Background:The evidence of the relationship between fiber intake and control of diabetes is mixed. The purpose of this study was to determine if an increase in dietary fiber affects glycosylated hemoglobin (HbA1c) and fasting blood glucose in patients with type 2 diabetes mellitus.Methods: Randomized studies published from January 1, 1980, to December 31, 2010, that involved an increase in dietary fiber intake as an intervention, evaluated HbA1c and/or fasting blood glucose as an outcome, and used human partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
150
1
17

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(172 citation statements)
references
References 37 publications
4
150
1
17
Order By: Relevance
“…Insoluble fiber plays an essential role in promoting regular bowel movement, which prevents constipation [33]. Fiber intake has also been correlated with the management of diabetes and the prevention of cardiovascular diseases, weight gain, and colorectal cancer [34][35][36].…”
Section: Proximate Compositionmentioning
confidence: 99%
“…Insoluble fiber plays an essential role in promoting regular bowel movement, which prevents constipation [33]. Fiber intake has also been correlated with the management of diabetes and the prevention of cardiovascular diseases, weight gain, and colorectal cancer [34][35][36].…”
Section: Proximate Compositionmentioning
confidence: 99%
“…As a biomarker reflecting an individual's average level of blood glucose over past 2-3 months, glycosylated haemoglobin A1c (HbA1c) has been associated with the risk of long-term diabetes complications (5) and used as the main indicator of glycaemic control status among diabetes patients (6) . The American Diabetes Association recommends an HbA1c level below 7?0 % as the goal of glycaemic control for diabetes patients (6) .There is sufficient evidence to support the role of dietary fibre in improving glycaemic control status in diabetes patients (7)(8)(9) . Evidence is also available for its beneficial effect on prevention of diabetes complications.…”
mentioning
confidence: 99%
“…Despite the mixed evidence of the relationship between fiber intake and control of diabetes, Post et al (2012), evaluated this relationship and demonstrated that fiber supplementation for type 2 DM can reduce fasting blood glucose and glycosylated hemoglobin in patients with type 2 DM. Increasing dietary fiber intake for diets for diabetic mellitus patients could be beneficial for disease management.…”
Section: Endogenous and Exogenous Management Of Ros Related Health Comentioning
confidence: 99%